China’s Foreign Security Strategy Through the Belt and Road Initiative Under Xi Jinping: Achievements and Challenges - Thang, Tran Duc; Kiet, Le Hoang (MultiTech Publisher, 2023)
After becoming General Secretary of the Communist Party of China in 2012, President Xi Jinping led the implementation of a comprehensive reform of the national security strategy. Among that, the foreign security strategy plays an extremely important role in China’s national security strategy under the leadership of President Xi Jinping to realize the goal of the “Chinese Dream”, rejuvenating the great Chinese nation. To achieve that goal, the Belt and Road Initiative (BRI) is the key strategy to help China rise to become a global superpower replacing the position of the US in the future. This paper uses a qualitative analysis method through secondary data collected in October 2023. The research results will provide an overview of the BRI. From there, the paper objectively and multidimensionally assesses the results achieved by the BRI so far, while reflecting the challenges currently and prospectively facing the BRI.